2004
DOI: 10.1530/rep.1.00060
|View full text |Cite
|
Sign up to set email alerts
|

A close correlation in the expression patterns of Af-6 and Usp9x in Sertoli and granulosa cells of mouse testis and ovary

Abstract: Usp9x, an X-linked deubiquitylating enzyme, is stage dependently expressed in the supporting cells (i.e. Sertoli cells and granulosa cells) and germ cells during mouse gametogenesis. Af-6, a cell junction protein, has been identified as a substrate of Usp9x, suggesting a possible association between Usp9x and Af-6 in spermatogenesis and oogenesis. In this study, we examined the expression pattern of Af-6 and Usp9x and their intracellular localization in testes and ovaries of mice treated with or without pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Acetonefixed cryosections were used for anti-PECAM1 and anti-TIE2 staining, whereas PFA-fixed, deparaffinized sections were used for anti-VCAM1-and anti-HIF1␣-staining. The reactions were visualized with an ABC kit (Vector Laboratories, CA) or Tyramide Signal Amplification kit (NEN Life Science Products, MA) as described previously (Sato et al, 2004). For in vivo quantification of angiogenesis, sections immunostained with anti-PECAM1 antibody were counterstained with hematoxylin.…”
Section: Immunohistochemistry and Immunoblottingmentioning
confidence: 99%
“…Acetonefixed cryosections were used for anti-PECAM1 and anti-TIE2 staining, whereas PFA-fixed, deparaffinized sections were used for anti-VCAM1-and anti-HIF1␣-staining. The reactions were visualized with an ABC kit (Vector Laboratories, CA) or Tyramide Signal Amplification kit (NEN Life Science Products, MA) as described previously (Sato et al, 2004). For in vivo quantification of angiogenesis, sections immunostained with anti-PECAM1 antibody were counterstained with hematoxylin.…”
Section: Immunohistochemistry and Immunoblottingmentioning
confidence: 99%
“…identities of the amino acid sequences of AFDN and USP9X were >80% and 97%, and the functional domains that presumably interact between AFDN and USP9X were found to be identical or nearly identical, suggesting that the expression patterns and biological functions of AFDN and USP9X in the pigs may be similar to those observed in mice [5,6].…”
Section: Discussionmentioning
confidence: 82%
“…Biochemical studies have reported interactions between USP9X and the cell adhesion and signaling molecules such as afadin and β-catenin in mammalian cells, and USP9X and AFDN biologically interact and co-localize at tight junctions in polarized MDCK II cells [7,15]. Interestingly, USP9X and AFDN, a substrate for USP9X are co-expressed at Sertoli cells and Sertoli-spermatid junctions at stages XI to VI when spermiation occurs, suggesting that the posttranslational regulation of AFDN by USP9X may control the intercellular adhesion dynamics in spermiogenesis [5]. Moreover, a loss of study showed that deuiquitinated USP9X is important during the transition from the mitotic to meiotic phase, and can result in male infertility [6].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these data suggest the potential function of USP9X in the testicular germ cells mainly before the early phase of meiosis. In addition, no appreciable USP9X-positive signals were previously shown to be detected in the spermatogenic cells in postnatal and adult testes (Noma et al 2002, Sato et al 2004. This discrepancy may be due to the lower sensitivity of the previous antibody to detect the USP9X-positive signals.…”
Section: Discussionmentioning
confidence: 89%